Nilai Indeks Fagositosis (IF) dan Total Vibrio Count (TVC) Udang Vaname (Litopenaeus vannamei) Pada Tambak Intensif - Putri Garnet Endo Mahata; Gunanti mahasri; Laksmi Sulmartiwi (Airlangga University, 2024)
Whiteleg shrimp (Litopenaeus vannamei) is one of the main fishery commodities since it has a high economic value. Vaname shrimp cultivated is done intensively where the stocking density and the amount of feed required are high. High stocking densities can trigger stress, increase possibility of physical contact among shrimps, and the spread of disease in shrimp becomes faster. The most common shrimp disease is Vibriosis where whiteleg shrimp are infected by Vibrio sp.. Whiteleg shrimp has an innate immunity system thus hemolymph has an important role in shrimp body defense. In this study, the research method used was purposive random sampling and was conducted from August to September 2023 by 50 shrimps sample. Assay of phagocytosis index (IF) which is a cellular response of the vaname shrimp body defense system was conducted at the Center for Brackish Water Aquaculture (BBPBAP) Jepara by applying a bacterial suspension of Staphylococcus sp. which has been attenuated and bacterial staining. Calculation of Total Vibrio Count (TVC) was conducted at the Laboratory of Bacteriology and Mycology, Faculty of Veterinary Medicine, Universitas Airlangga, by using TCBS (Thiosulfate Citrate Bile Salt Sucrose Agar) agar media from Vibrio sp. bacteria cultured from the hepatopancreas of shrimp samples. The results showed that vaname shrimp cultured in intensive ponds were infected with Vibrio sp. with a TVC value of 3.3x105 cfu/ml and an IF value of 0.87.